Grid Integration Requirements for Variable Renewable Energy - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2019)
This technical guide is the first in a series of four technical guides on variable renewable energy (VRE) grid integration produced by the Energy Sector Management Assistance Program (ESMAP) of the World Bank and the Global Sustainable Electricity Partnership (GSEP). It provides a general overview of the intrinsic characteristics of VRE generation, mainly solar PV and wind, what the main challenges are along with some recommendations for VRE technical specifications, applicable standards, and essential testing. The main focus of the document presents a detailed outline of the essential requirements for VRE integration into the power grid. The requirements differ for different levels of penetration but would require fundamental grid compliance requirements that must be reflected in any grid. This document provides these requirements along with recommendations of advanced VRE integration requirements that could be reflected in the power system operations with these VRE resources. The compliance with the technical requirements where applicable is validated through extensive series of interconnection studies which are further elaborated in "STUDIES FOR GRID CONNECTION OF VARIABLE RENEWABLE ENERGY GENERATION PLANTS – Technical Guide 3".